Safety and Efficacy of Spinal Anaesthesia for Ureteroscopy and in Situ Lithotripsy in Proximal Solitary Pelvic Stones: Spinal Anesthesia in Situ Lithotripsy in Proximal Solitary Pelvic Stones - Ashfaq, Shumaila; Sabir, Sara; Niazi, Rehan Hassan Khan; Channa, Aftab Ahmed; Kazmi, Itrat Hussain; Asghar, Hafiz Faheem (Pakistan Journal of Health Sciences, 2025)
Ureteroscopy and in situ lithotripsy provide an alternative treatment for patients with proximal solitary pelvic stones, but their safety and efficacy using spinal anesthesia are poorly studied. Objectives: To evaluate the safety, efficacy and patient satisfaction with spinal anesthesia during these procedures. Methods: A single-arm, prospective observational study was conducted at Islam Medical College, Sialkot, from May to October 2024, involving a total of 81 patients aged 20 to 60 years, ASA class I to III, who underwent elective ureteroscopy or lithotripsy. 15 mg of 0.75% bupivacaine was used to perform spinal anesthesia at the L3-L4 interspace. The main endpoints were success, complications, recovery times, and patient satisfaction. Other secondary outcomes were intraoperative hypotension, bradycardia, pain as measured by visual analogue scale (VAS) and post-dural puncture headache (PDPH). SPSS version 26.0 was used for statistical analysis. Results: A total of 97.5% patients completed the procedure under spinal anesthesia. The mean procedure time was 37.4 ± 6.2 min. In 53.1% of patients, the maximum sensory blockade level was T6. Hypotension (14.8%), bradycardia (6.2%), and PDPH (2.5%) were the complications. Next, postoperative pain significantly decreased over the 24 hours. In 55.6% of patients, excellent satisfaction was observed. Mean recovery time was 165.3 ± 22.4 minutes. Conclusions: Overall, spinal anesthesia for ureteroscopy and in situ lithotripsy in patients with proximal solitary pelvic stones is safe, effective, and has a high patient satisfaction rate.